The wrath of angels : a Charlie Parker thriller - Connolly, John, 1968- (Connolly, John, 1968- Charlie Parker thriller., 2013)
Racing against a serial killer in the depths of the Maine woods, private detective Charlie Parker searches for a secret list of names in the wreckage of a plane that has never been reported missing.